Genes involved in amelogenesis imperfecta. Part II - Víctor Hugo Simancas-Escorcia; Alfredo Enrique Natera-Guarapo; María Gabriela Acosta-de Camargo (Universidad de Antioquia, 2019)
Amelogenesis imperfecta (AI) is a condition of genetic origin that alters the structure of tooth enamel. AI may exist in isolation or associated with other systemic conditions as part of a syndromic AI. Our goal is to describe in detail the genes involved in syndromic AI, the proteins encoded by these genes, and their functions according to current scientific evidence. An electronic literature search was carried out from the year 2000 to December 2017, pre-selecting 1,573 articles, 40 of which were analyzed and discussed. The results indicate that mutations in 12 genes are responsible for syndromic AI: DLX3, COL17A1, LAMA3, LAMB3, FAM20A, TP63, CNNM4, ROGDI, LTBP3, FAM20C, CLDN16, CLDN19. These genes participate in the coding of proteins involved in phosphorylation, ion exchange, and production and degradation of the constituent elements of the mineral and organic phase of tooth enamel. The scientific evidence confirms that AI can be part of the syndrome and requires special attention from the medical-dental community.